2010
DOI: 10.1111/j.1439-0418.2009.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Host suitability of UV‐irradiated eggs of three Lepidoptera species for rearing Trichogrammatoidea lutea Girault (Hymenoptera: Trichogrammatidae)

Abstract: To develop a rearing programme for the egg parasitoid Trichogrammatoidea lutea for augmentative biological control, the effects of ultraviolet (UV) irradiated host eggs were evaluated on the number of eggs parasitized, development time, number of progeny and sex ratio of T. lutea, using eggs of the lepidopteran species Helicoverpa armigera, Chilo partellus and Cadra cautella as hosts. UV‐irradiation of 13 min was sufficient to kill embryos of all three hosts. The highest mean percentage parasitism on UV‐irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…Our no-choice tests demonstrated that the three Trichogramma parasitoids, especially T. japonicum and T. leucaniae, had comparable parasitism on fertilized and UVF-treated C. cephalonica eggs, which was similar to previous findings on L. botrana, H. armigera, and E. kuehniella hosts (Moreno et al, 2009;Mawela et al, 2010;St-Onge et al, 2014). However, our choice test was the first to show that Trichogramma parasitoids preferred UVF hosts over fertilized or unfertilized hosts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our no-choice tests demonstrated that the three Trichogramma parasitoids, especially T. japonicum and T. leucaniae, had comparable parasitism on fertilized and UVF-treated C. cephalonica eggs, which was similar to previous findings on L. botrana, H. armigera, and E. kuehniella hosts (Moreno et al, 2009;Mawela et al, 2010;St-Onge et al, 2014). However, our choice test was the first to show that Trichogramma parasitoids preferred UVF hosts over fertilized or unfertilized hosts.…”
Section: Discussionsupporting
confidence: 88%
“…All Trichogramma parasitoids developed slowest on unfertilized hosts. Trichogramma japonicum or T. leucaniae had similar developmental times on fertilized and UVF-treated C. cephalonica eggs, which was like the results of T. cacoeciae on freshly laid L. botrana eggs, and of T. lutea on eggs of H. armigera, C. partellus, and C. cautella (Moreno et al, 2009;Mawela et al, 2010). A previous study showed that gamma-irradiated hosts did not affect developmental time of T. evanescens and Trichogrammatoidea bacterae Nagaraja (El-Mandarawy & Rizk, 2002).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…By contrast, the more ecological literature on host‐mediated effects on herbivory deals with UV‐B and largely with chewing insects, especially caterpillars (Ballaré et al 1996, 2011, Rousseaux et al 2004, Caputo et al 2006, Foggo et al 2007). While there are points of overlap between these research areas, for example the role of UV‐B in thrip vision and behavior (Mawela et al 2010) or of host quality on aphids (Kuhlmann and Müller 2009, 2010b), the general lack of integration in research into UV effects on crop–herbivore interactions is a significant constraint in obtaining a solid overview of how a particular UV environment might contribute to the totality of plant–herbivore interactions. Of course, these effects of plant–herbivores interactions need also to be considered in the context of the wider effects of UV manipulation, not least if UV responses are to be effectively exploited in horticulture.…”
Section: Discussionmentioning
confidence: 99%
“…armigera eggs were obtained from a culture maintained at the Agricultural Research Council (Pretoria, South Africa). This culture was established with specimens collected from the Springbok Flats (29°40 0 S 17°53 0 E) in 1974 and supplemented in 2006 with specimens collected from cotton plants near Groblersdal (25°15 0 S 29°25 0 E) in Mpumalanga, South Africa (Mawela et al, 2010). Larvae were reared in our laboratory on a wheat-germ based artificial diet (Bot, 1966).…”
Section: Insectsmentioning
confidence: 99%